Enzymatic Biosynthesis of Simple Phenolic Glycosides as Potential Anti-Melanogenic Antioxidants - Hogwuan Jung; JaeWook Oh; Younghae Kwon; Woongshin Kang; Minsuk Seo; Yurin Seol; Je Won Park (MDPI AG, 2022)
Simple phenolics (SPs) and their glycosides have recently gained much attention as functional skin-care resources for their anti-melanogenic and antioxidant activities. Enzymatic glycosylation of SP aglycone make it feasible to create SP glycosides with updated bioactive potentials. Herein, a glycosyltransferase (GT)-encoding gene was cloned from the fosmid libraries of Streptomyces tenjimariensis ATCC 31603 using GT-specific degenerate PCR followed by in silico analyses. The recombinant StSPGT was able to flexibly catalyze the transfer of two glycosyl moieties towards two SP acceptors, (hydroxyphenyl-2-propanol [HPP2] and hydroxyphenyl-3-propanol [HPP3]), generating stereospecific α-anomeric glycosides as follows: HPP2-O-α-glucoside, HPP2-O-α-2"-deoxyglucoside, HPP3-O-α-glucoside and HPP3-O-α-2"-deoxyglucoside. This enzyme seems not only to prefer UDP-glucose and HPP2 as a favorable glycosyl donor and acceptor, respectively but also differentiates the positional difference of the hydroxyl function as acceptor catalytic sites. Paired in vitro and in vivo antioxidant assays represented SPs and their corresponding glycosides as convincing antioxidants in a time- and concentration-dependent manner by scavenging DPPH radicals and intracellular ROS. Even compared to the conventional agents, HPP2 and glycoside analogs displayed improved tyrosinase inhibitory activity in vitro and still suppressed in vivo melanogenesis. Both HPP2 glycosides are further likely to exert the best inhibitory activity against elastase, eventually highlighting these glycosides with enhanced anti-melanogenic and antioxidant activities as promising anti-wrinkle hits.